EFEKTIFITAS RATIONAL EMOTIVE BEHAVIOR THERAPY DALAM MENANGGULANGI BERBAGAI - Fitri, Aulia; Fitriani, Wahidah (UNIVERSITAS RIAU KEPULAUAN, BATAM, INDONESIA, 2020)
The purpose of this article is to see the extent to which therapeutic emotive behavior can alleviate anxiety in the client. The method used is the study of literature where the authors use the study of literature on the variables discussed. The results are that Andi Thahir's research, Dede Rizkiyani (2016) found the results of research that a person experiences a decrease in anxiety facing the future through the REBT approach. Research Eva, Karyono Dian (2010) found the results of research that a person experiences a decrease in anxiety facing the future on the use of drugs through the REBT approach. Research Praise, Hafiz, Randi (2019) found the results of research that the REBT counseling approach can overcome culture shock in overseas students. Research Dwi, Fuad Retno (2011) found the results of research that the REBT approach can improve the quality of life of people with diabetes mellitus. Research Vivi, Ike (2018) found the results of research that REBT can overcome parental anxiety about the future of children with mental retardation. Based on the above explanation it can be understood that the behavioral therapy approach is effective in alleviating various anxiety.